2005
DOI: 10.1002/ajmg.b.30154
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the brain derived neurotrophic factor gene in Alzheimer's disease

Abstract: Genes known to contribute to the genetic predisposition to Alzheimer's disease (AD) are active in pathways of neurodegeneration but explain only a minority of the genetic contribution to AD. A protein of importance in cerebral neurodegeneration is the brain-derived neurotrophic factor (BDNF). Variations in two single-nucleotide polymorphisms (SNPs) within the BDNF gene have previously been associated with AD, and one of these SNPs has also been associated with memory loss and affective disorders. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Previous studies have reported five positive results (12-16) and 21 negative results (19,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) between the BDNF Val66Met polymorphism and AD. In the present meta-analysis, no significant association was found between BDNF Val66Met and AD (P>0.05, Table II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported five positive results (12-16) and 21 negative results (19,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) between the BDNF Val66Met polymorphism and AD. In the present meta-analysis, no significant association was found between BDNF Val66Met and AD (P>0.05, Table II).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous carriers of the T-allele tend to have a higher risk of developing AD than non-carriers (36). There have been a total of four significant results (13,(17)(18)(19)) and 14 non-significant results (28)(29)(30)(31)(34)(35)(36)(37)40,41,(43)(44)(45) among the previous association studies between the BDNF C270T polymorphism and AD. In the present meta-analysis, the BDNF C270T polymorphism was found to increase the risk of AD by 88% in Asians under the dominant model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the decline in BDNF in AD, the potential specificity of the decline in BDNF to temporal structures like hippocampus, and the decline in estradiol in women with age (and of course complete loss of serum estradiol after menopause), one logical hypothesis is that Alzheimer's disease is due to the reduction of estrogen-induced BDNF synthesis in hippocampus. Indeed, genetic studies to date do not provide robust evidence that there is a genetic component (a contribution of BDNF polymorphisms to the disease [126][127][128][129][130]), suggesting estrogen-BDNF interactions may be intact, but there simply may be too little estrogen to adequately maintain BDNF levels, leading to reduced signaling. This hypothesis is supported by the evidence that estradiol administration restores cognitive function in ovariectomized animals and in animal models of AD [124].…”
Section: Implications For Neurological and Psychiatric Disease A mentioning
confidence: 99%
“…BDNF levels are decreased in Alzheimer's disease (AD) [30][31][32][33] and, interestingly, the Val not the Met allele has been associated with increased risk of AD. 34,35 Other studies have failed to replicate such an association [36][37][38][39][40] and a recent study suggested that homozygosity for the Val allele is protective against AD in female subjects. 41 As AD is characterized by memory and other cognitive deficits, genes associated with the disease are also good candidates for association with non-pathological cognitive aging.…”
Section: Introductionmentioning
confidence: 99%